2014
DOI: 10.1371/journal.ppat.1003991
|View full text |Cite
|
Sign up to set email alerts
|

Fha Interaction with Phosphothreonine of TssL Activates Type VI Secretion in Agrobacterium tumefaciens

Abstract: The type VI secretion system (T6SS) is a widespread protein secretion system found in many Gram-negative bacteria. T6SSs are highly regulated by various regulatory systems at multiple levels, including post-translational regulation via threonine (Thr) phosphorylation. The Ser/Thr protein kinase PpkA is responsible for this Thr phosphorylation regulation, and the forkhead-associated (FHA) domain-containing Fha-family protein is the sole T6SS phosphorylation substrate identified to date. Here we discovered that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 60 publications
4
74
0
Order By: Relevance
“…DotU (TssL) proteins localize to the inner membrane and serve as a critical component of the T6S anchor module (Durand et al ., ; Zoued et al ., ). A. tumefaciens TssL is phosphorylated solely at T14 by PpkA (Lin et al ., ) (Supporting information Fig. S7A).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…DotU (TssL) proteins localize to the inner membrane and serve as a critical component of the T6S anchor module (Durand et al ., ; Zoued et al ., ). A. tumefaciens TssL is phosphorylated solely at T14 by PpkA (Lin et al ., ) (Supporting information Fig. S7A).…”
Section: Resultsmentioning
confidence: 97%
“…In A. tumefaciens phosphorylated TssL (DotU) interacts with Fha, a forkhead‐associated domain‐containing protein, and this phosphorylation dependent interaction is required for T6S activity (Mougous et al ., ; Lin et al ., ). Indeed, we found that EPGS mutants harbouring either a deletion of fha2 (Δ fha2 ) or the substitution of conserved Fha2 residues implicated in phosphopeptide binding (Arg 36 and Ser 52) with alanine (R36A S52A) (Supporting information Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A mechanism of posttranslational activation, named the threonine phosphorylation pathway (TPP), has been described in P. aeruginosa and Agrobacterium tumefaciens. It requires sensing and signaling of the attack by the TagQRST proteins, leading to the PpkA-dependent phosphorylation of a forkhead-associated protein (FHA) or of the TssL T6SS core component and, ultimately, to the activation of the late stages of T6SS assembly (93)(94)(95)(96)(97). However, no homologue subunits to the TagQRST-PpkA-PppA-FHA threonine phosphorylation pathway are encoded within the S. Typhimurium SPI-6 T6SS gene cluster, suggesting that the mechanism of sensing and posttranslational activation is different from that described in P. aeruginosa or A. tumefaciens.…”
Section: Discussionmentioning
confidence: 99%
“…Agrobacterium tumefaceins C58 harbors one T6SS that is activated transcriptionally by an ExoR-ChvG/ChvI signaling cascade and posttranslationally via threonine phosphorylation when sensing acidity (34)(35)(36). Three type VI effectors, namely type VI amidase effector (Tae) and type VI DNase effectors (Tde1 and Tde2), confer antibacterial activity of this bacterium.…”
Section: Significancementioning
confidence: 99%